Absence of aberrant myeloid progenitors by flow cytometry is associated with favorable response to azacitidine in higher risk myelodysplastic syndromes. Issue 3 (28th January 2014) - Alhan, Canan; Westers, Theresia M.; van der Helm, Lieke H.; Eeltink, Corien; Huls, Gerwin; Witte, Birgit I.; Buchi, Francesca; Santini, Valeria; Ossenkoppele, Gert J.; van de Loosdrecht, Arjan A.
<x xml:space="preserve">Abstract</x> Background In intermediate‐2 (Int‐2) and high risk patients with myelodysplastic syndromes (MDS), treatment with azacitidine is associated with hematological improvement and prolonged overall survival (OS) in patients who respond to therapy. However, only half of the patients who are treated will benefit from this treatment. It is a major challenge to predict which patients are likely to respond to treatment. The aim of this study was to investigate the predictive value of immunophenotyping for response to treatment with azacitidine of Int‐2 and high risk MDS patients. Methods Bone marrow aspirates were analyzed by flow cytometry in 42 patients with Int‐2 and high risk MDS, chronic myelomonocytic leukemia, or low blast count acute myeloid leukemia before treatment and after every third cycle of azacitidine. A flow score was calculated using the flow cytometric scoring system (FCSS). Results The presence of myeloid progenitors with an aberrant immunophenotype was significantly associated with lack of response (p = 0.02). A low pretreatment FCSS was associated with significantly better OS compared with a high pretreatment FCSS (p = 0.03). A significant decrease in FCSS was observed in patients with complete response after three cycles azacitidine compared to patients with progressive disease (p = 0.006). Conclusions Absence of aberrant myeloid progenitor cells at baseline and/or a decrease in the FCSS during treatment identified Int‐2 and high risk MDS patients who are likely to respond to treatment with azacitidine. © 2014 International Clinical Cytometry Society